Constraints and opportunities for market-based finance for the restoration and protection of blue carbon ecosystems. (September 2019) - Vanderklift, Mathew A.; Marcos-Martinez, Raymundo; Butler, James R.A.; Coleman, Michael; Lawrence, Anissa; Prislan, Heidi; Steven, Andrew D.L.; Thomas, Sebastian
Abstract: The restoration and protection of "blue carbon" ecosystems – mangroves, seagrasses, and tidal marshes – has potential to offset greenhouse gas emissions and improve coastal livelihoods. However, realisation of this potential relies on global investment in restoration and protection, which in turn relies on appropriate funding mechanisms that are currently impeded by multiple constraints. Constraints include commercial considerations by private investors (including reliable estimates of financial returns, risk quantification and management, and supply chain impacts), regulatory and legal uncertainty (such as the complexity of property rights in coastal areas, policy coordination across jurisdictions, and stable policy consistent with the duration of blue carbon projects). There are, however, opportunities to improve on current practices, including better stakeholder engagement (including social license to operate, and knowledge transfer to promote best practices), and targeted use of public and philanthropic funding (to subsidise demonstration projects, reduce financial risk through collaterals, and promote low-profit but high co-benefit projects). In this paper, a strategy for the realisation of potential benefits through commercially viable and scientifically robust blue carbon initiatives is presented alongside insights and guidance for the policy, research, civil society, and private sectors to achieve these important long-term outcomes.